PENGUATAN KEMANDIRIAN EKONOMI PESANTREN MENUJU INDONESIA EMAS 2045 - Rusdan, Rusdan (Jurnal El-Hikam, 2023)
"Pesantren" is one of the crucial pillars of the state. Considering its existence, this institution has played a significant role in nation-building long before Indonesia gained independence. Its inception was laid in 1399 by Sheikh Maulana Malik Ibrahim. In subsequent periods, pesantren has continued to undergo improvements and strengthening, including enhancing economic self-reliance. The main issue examined in this research pertains to the economic self-reliance of pesantren, with three derivative issues: firstly, how urgent is the strengthening of pesantren's economic self-reliance; secondly, what are the obstacles and opportunities for strengthening pesantren's economic self-reliance; and thirdly, what strategic steps must pesantren take to reinforce its economic self-reliance. This research falls under qualitative research with an emphasis on literature study. All data used in this research are secondary data, which are of the second-hand type, including books, scholarly articles, newspapers, and the like. From a series of studies conducted, it can be concluded that pesantren needs to strengthen its economic self-reliance. This is primarily to ensure its independence and the flexibility to carry out various activities. The obstacles faced by pesantren in strengthening their economic self-reliance stem from both internal and external factors. Internal factors are more influenced by motivation and needs, while external factors are more influenced by cultural factors and upbringing. The steps taken by pesantren to strengthen their economic self-reliance include assessing potential and resources, strategic planning, income diversification, entrepreneurship education, prudent financial management, strengthening partnerships and networks, marketing expansion and promotion, transparency, and controlled and measurable risk management.